Improved selection for inositol-utilization following transformation of Neurospora crassa - Robert L Metzenberg (Fungal Genetics Reports, 2002)
Plasmids based on the cloned inositol gene of Neurospora crassa are potentially very useful as a transformation marker, or for techniques like insertional mutagenesis.